Risk Management Concept: Predictive Assessment in Transhumanistic Space - Vorontsova, Yulia; Gil Martínez, Maria Adelaida; Arakelyan, Artur (Տիգրան Մեծ)
At the present stage of realizing the transhumanistic concept, its reflection in various fields of scientific knowledge should be considered, considering the possible risks formed by the transhumanistic space. This concept provokes interest both for its direction and its contradictions. The article considers alternative concepts and tools different from transhumanism in their moral and ethical directionality and based on responsible decisions that take this aspect into account. The concept of risk management is presented based on the diagnostics of orienting indicators that outline the transhumanistic space according to the indicated risk zones. The diagnostic analysis is based on a predictive assessment of the development of the situation, which is formed as a result of using innovative technologies/biotechnologies from the point of transhumanism. Several exact directions for the assessment‟s development of the situation developing in the transhumanistic space are identified, conceptual decisions that develop such assessment are presented, and the interconnection between the blocks of the methodology for modelling future decisions to respond to emerging challenges of transhumanism is given.
Keywords: Philosophy of economics